Morphological Characteristics and Correction of Long Tubular Bone Regeneration under Chronic Hyperglycemia Influence - Yevhenii S. Dudchenko; Olena S. Maksymova; Vasyl S. Pikaliuk; Dmytro V. Muravskyi; Ludmila I. Kyptenko; Gennadii F. Tkach (Analytical Cellular Pathology)
Introduction. Unsatisfactory consequences of bone regeneration disorders in diabetes mellitus (DM) patients, their high prevalence, complication number, and difficulties in treatment require further study and deeper understanding of reparative osteogenesis mechanisms under chronic hyperglycemia and finding new effective and affordable approaches to their treatment. Therefore, the aim of our work was to study the histological, ultramicroscopic, and histomorphometric features of reparative osteogenesis in rats with chronic hyperglycemia (CH), as well as to investigate the possibility of platelet-rich plasma (PRP) use in a fracture area in order to correct the negative effects of CH on reparative osteogenesis processes. Study Object and Methods. The studies were performed on 70 white laboratory rats, mature males, which were divided into the following groups: control group, animals with posttraumatic tibial defect under conditions of CH exposure, rats with experimental CH that were administered with PRP into the bone defect, and animals for the assessment of glucose homeostasis and confirmation of simulated CH. Light microscopy was performed using an Olympus BH-2 microscope (Japan). Ultramicroscopic examination was performed using REM-102 scanning electron microscope. The statistical analysis was performed using SPSS-17 software package. Results. The formation of new bone tissue in animals with CH did not occur after two weeks. Only on the 30th day of reparative osteogenesis the newly formed woven bone tissue was 61.54% of the total regenerated area. It was less than the reference value by 22.89% (P<0.001). On the 14th day of reparative osteogenesis, the regenerated area in a group of animals with CH and PRP injection consisted of connective tissue by 68.94% (4.94% less than in animals with CH (P<0.001)) and woven bone tissue by 31.06%, (13.51% less than in the control group (P<0.001)). On the 30th day, the area of woven bone tissue in a regenerate of this group was less than that of the control group by 12.41% (P<0.001). Conclusion. Thus, chronic hyperglycemia contributes to inflammation delay within the bone defect site, which makes the process of reparative osteogenesis more prolonged. The results of chronic hyperglycemia effect on bone regeneration are also impairment of osteogenic cell proliferation and shift of their differentiation towards the fibrocartilage regenerate formation. The PRP corrects the negative impact of chronic hyperglycemia on reparative osteogenesis, promoting more rapid inflammatory infiltrate removal from the bone defect site and osteogenic beam formation and remodeling of woven bone into lamellar membranous bone tissue.